Janus Kinase-2 V617F Mutation and Antiphospholipid Syndrome in Cerebral Sinus Venous Thrombosis: Natural History and Retrospective Bicenter Analysis - Orion, David; Itsekson-Hayosh, Ze'ev; Peretz, Shlomi; Mendel, Rom; Yaniv, Gal; Attia, Moshe; Grizim-Merkel, Drorit (Frontiers in Neurology, 2022)
Background: Cerebral sinus venous thrombosis (CSVT) is a rare neurovascular entity, usually associated with acquired or genetic hypercoagulable states. In up to 30% of cases it remains idiopathic. Bone marrow proliferation disorders that are associated with Janus Kinase 2 V617F mutation (JAK-2) are known causes of systemic and cerebral thrombosis—at times despite normal blood counts—for which hematologic treatment exists. However, JAK-2 prevalence in CSVT cases is not clear. Methods: In this retrospective analysis, data of 236 CSVT patients admitted to two tertiary centers between 2010-2020 were analyzed, with emphasis on laboratory and imaging data and clinical and interventional outcome. Results: 236 patients were included in the analysis. Patient's median age was 42 years and average age was 44 (±19), with 59% female patients. JAK-2 positivity rate was 18% (among 77 patients tested for the mutation). Patients with normal blood counts on presentation comprised 36% of JAK-2 positive cases. Other hypercoagulability states were also investigated, with anti-phospholipid syndrome (APLA) showing the highest prevalence (11%) followed by other etiologies including oral contraceptive use, Factor V Leiden, prothrombin mutation and malignancy. Selected JAK-2, APLA and prothrombin mutation cases showed a more severe clinical course. Conclusions: The JAK-2 mutation is underdiagnosed and its screening may be warranted in cases of idiopathic CSVT, even despite normal blood counts, to allow disease-modifying treatment and blood cell count monitoring. JAK-2, APLA and prothrombin mutation might be associated with a more complicated clinical course.